Ruptured metastatic liver tumor secondary to a thymoma: a case report. Issue 8 (14th August 2021) - Utsunomiya, Takeshi; Sakamoto, Katsunori; Tsukamoto, Daiki; Shine, Mikiya; Nishi, Yusuke; Matsui, Takashi; Tamura, Kei; Inoue, Hitoshi; Takai, Akihiro; Ogawa, Kohei; Sunago, Kotaro; Hiasa, Yoichi; et al.
Abstract: We report a case of rupture of a synchronous metastatic liver tumor secondary to a thymoma. A 56-year-old woman was referred to our hospital with acute abdomen. Computed tomography (CT) revealed a 10 cm diameter tumor in the left lateral segment of the liver, together with ascites, which was suggestive of intra-abdominal bleeding. She was in stable condition and hemostasis was confirmed by angiography. CT also revealed a mass in the anterior mediastinum. Elective laparoscopic left lateral segmentectomy was performed to make a pathological diagnosis and for radical resection. No peritoneal dissemination was observed and the liver tumor was curatively resected. The patient subsequently underwent thymectomy. The pathological diagnoses were thymoma with the liver metastasis. Currently, at 30 months post-treatment, she has had no tumor recurrence. Rupture of a metastatic liver tumor secondary to a thymoma is a rare condition; careful preoperative management and aggressive treatment might improve the patient's prognosis.